2017
DOI: 10.1002/hec.3479
|View full text |Cite
|
Sign up to set email alerts
|

Linking the Regulatory and Reimbursement Processes for Medical Devices: The Need for Integrated Assessments

Abstract: Much criticism has been directed at the licencing requirements for medical devices (MDs) as they often result in a lack of robust evidence to inform health technology assessment (HTA) decisions. To better understand the current international decisional framework on MD technologies, we undertook three linked research studies: a review of the device regulatory procedures, a survey of current HTA practices and an empirical comparison of HTA reports of drugs versus MDs. Our review confirms that current device regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 34 publications
0
49
0
2
Order By: Relevance
“…case series, case studies and manufacturers' reports) and provided indications on safety and efficacy only. This finding clearly illustrates some of the typical challenges of assessing MDs, such as the lack of evidence at the time of market approval and the relevance of collecting post‐marketing evidence, accompanied by an iterative process to assess the new evidence as it is generated (Drummond et al ., ; Tarricone et al ., ; Ciani et al ., ). Interestingly, although the lack of evidence leads to difficulties in conducting full HTAs, this does not seem to have delayed the uptake of TAVI in Europe, where the yearly implant rate grew by 815% in the first 5 years, that is before its use in any indication was formally recommended by HTA agencies.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…case series, case studies and manufacturers' reports) and provided indications on safety and efficacy only. This finding clearly illustrates some of the typical challenges of assessing MDs, such as the lack of evidence at the time of market approval and the relevance of collecting post‐marketing evidence, accompanied by an iterative process to assess the new evidence as it is generated (Drummond et al ., ; Tarricone et al ., ; Ciani et al ., ). Interestingly, although the lack of evidence leads to difficulties in conducting full HTAs, this does not seem to have delayed the uptake of TAVI in Europe, where the yearly implant rate grew by 815% in the first 5 years, that is before its use in any indication was formally recommended by HTA agencies.…”
Section: Discussionmentioning
confidence: 97%
“…In a further paper, included in this supplement (Ciani et al ., ), a sample of HTA reports were analysed in order to assess whether there were any key differences in the methods applied in the HTA of devices as compared with drugs. They found that there were several differences in the types of clinical studies forming the basis for the HTAs, how the health problem and use of the technology were considered, the description and technical characteristics of the technology and the consideration of the organisational aspects of the use of the technology.…”
Section: Introductionmentioning
confidence: 99%
“…In their paper in this supplement, Ciani et al (2017) argue that (i) more stringent requirements supported by appropriate methodological choices are needed to provide clinical trial data for high-risk devices; (ii) post-marketing surveillance based on device and user real world data should be encouraged; (iii) international harmonization of practices will benefit the manufacturers and (iv) progressive alignment of regulatory and HTA evaluation for parallel submissions will improve efficiency in the health systems and promote timely access to affordable effective technologies.…”
Section: Improving the Process For Hta Of Medical Devicesmentioning
confidence: 96%
“…In the second paper in this supplement, Ciani et al () focus on the second phase of their research, in which they analysed a sample of HTA reports in the field of cardiovascular disease in order to assess whether there are any key differences in how methods are applied. They found that there were several differences, in the types of clinical studies forming the basis for the HTAs, how the health problem and use of the technology were considered, the description and technical characteristics of the technology and the consideration of the organizational aspects of the use of the technology.…”
Section: Cross‐country Analysis Of Regulation and Hta Of Medical Devicesmentioning
confidence: 99%